Experimental determination of suboptimal parameters for energy-efficient control of an induction motor - Valentina S. Goun; Aleksandr S. Anikin; Aleksey A. Bakin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The article presents the results of experimental studies of the automatic speed control system (ASCS) of an induction motor (IM). Preliminary experimental studies have shown that the stator current minimum (power factor) is a suboptimal criterion. Optimal in terms of control is the rated power factor. Tests of IM with a thyristor voltage converter (TVC), as a power source, were conducted on an installation created at the department. A mathematical model of ASCS IM corresponding to the experimental setup has been developed. To determine the main functional dependences of IM, such as stator voltage, stator current, power factor, torque on the shaft, a program for approximating experimental data by polynomials was developed. Using the developed mathematical model, the regulatory characteristic of IM that was optimal from an energy point of view was obtained. The necessary indicators of IM and TVC are determined (thyristor control angle, stator voltage, stator current) to change existing settings in order to save electric energy. The results of experimental studies are presented, the graph shows an optimized version of the form of the regulatory characteristic according to the criterion of minimum electric energy consumption.